Acute acalculous cholecystitis complicating chemotherapy for acute myeloblastic leukemia - Kassar, Olfa (Leuk Res Rep, 2015)
Acute acalculous cholecystitis is a rare complication in the treatment of acute myeloblastic leukemia. Diagnosis of acute acalculous cholecystitis remains difficult during neutropenic period. We present two acute myeloblastic leukemia patients that developed acute acalculous cholecystitis during chemotherapy-induced neutropenia. They suffered from fever, vomiting and acute pain in the epigastrium. Ultrasound demonstrated an acalculous gallbladder. Surgical management was required in one patient and conservative treatment was attempted in the other patient. None treatment measures were effective and two patients died. Acute acalculous cholecystitis is a serious complication in neutropenic patients. Earlier diagnosis could have expedited the management of these patients.